The nutrition and life-style of mothers from industrial and nonindustrial regions related to their economic situation - Ingrid Baloun; Olga Dvorackova; Simona Simkova; Radim J Sram (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
Aim: The study analyzed the nutrition and lifestyle of mothers related to air pollution in industrial and non-industrial regions, taking into account the economic situation of households. Methods: The respondents were a deliberate sample of mothers from two regions of the Czech Republic - districts of Ceske Budejovice (CB, N=376) and Karvina (KA, N=449). Selected districts were chosen for their difference in the air pollution, with CB being one of the least polluted and KA one of the most polluted regions/districts in the Czech Republic. Data were collected in maternity hospitals in the years 2019 and 2020. Results: The majority of respondents (98.5%) described their economic situation at least as average. They also consumed daily at least one hot meal. In Karvina mothers more often eat fish, poultry, legumes and also sweet meals and fried food than in Ceske Budejovice, where are more often consumed dairy products. Information about health risk are important for change of their habits. Conclusion: Most mothers in our study subjectively evaluated their economic situation as moderately good in both regions. Better economic situation was correlated with healthy nutrition, including higher consumption of fruits and vegetables, wholegrain bread, beef and fish and lower consumption of sweet drinks and produced meats. Notably the consumption of fruits and vegetables in the industrial region has risen in comparison with previous data, which is an improvement promising a better starting position for the new generation.